Nano-grained SnO2/Li4Ti5O12 composite hollow fibers via sol-gel/ electrospinning as anode material for Li- ion batteries. (June 2017) - Haridas, Anulekha K.; Sharma, Chandra S.; Hebalkar, Neha Y.; Rao, Tata N.
Abstract: The high capacity of SnO2 (tin oxide) and high rate capability of Li4 Ti5 O12 (lithium titanate, LTO) were pooled together for engineering a composite Li ion anode material in hollow fiber edifice by sol-gel/electrospinning. The electrospun porous precursor composite hollow fibers (CHFs) were heat treated either in air (SnO2 /LTOA ) or argon (SnO2 /LTOAr ) atmosphere to control grain size, porosity and presence of Ti 3+ content. The morphological study performed using Field Emission Scanning Electron Microscopy and Transmission Electron Microscopy revealed smaller grain size (5–10 nm) for SnO2 /LTOAr CHFs. Further, X-Ray Diffraction and X- Ray Photoelectron Spectroscopy studies illustrated a significant variation in the crystallinity and the elemental oxidation states in these CHFs respectively. Brunauer-Emmett-Teller measurements exposed the presence of high surface area and pore volume in SnO2 /LTOAr CHFs. Further, the half-cell galvanostatic charge-discharge performances of SnO2 /LTOAr CHFs at 1 C rate revealed a stable specific capacity of 300 mA h/g for 110 cycles with 90% capacity retention. The stable and high capacity of SnO2 /LTOAr CHFs were corroborated to the presence of smaller grain size, high porosity and conductive Ti 3+ providing faster lithium ion diffusion when compared to SnO2 /LTOA CHFs. Electrochemical Impedance Spectroscopy study confirmed low impedances in SnO2 /LTOAr CHFs due to low charge transfer and electrolyte resistances. Moreover, Li ion full-cell study performed using LiFePO4 (LFP) cathode (3 V), delivered a specific capacity of 230 mAh/g at 0.1 C rates. The excellent electrochemical performance of SnO2 /LTOAr CHFs in both half-cell and full-cell modes illustrated the significance of sol-gel/electrospinning in synthesizing high performance Lithium ion batteries in a cost effective and scalable way. Graphical abstract: Highlights: SnO2 /LTO composite (CHF) Li-ion anode is synthesised by sol-gel/electrospinning. CHF annealed either in air or argon to control grain size, porosity & Ti 3+ content. SnO2 /LTOAr CHF retained 90% of initial capacity in the half-cell mode. SnO2 /LTOAr CHF with LiFePO4 full-cell is a high energy density 3 V battery. SnO2 /LTOAr CHF is a new scalable anode design for high performance Li-ion batteries.